Investigation of quercus infectoria (qi) methanolic extract cytotoxicity effect on glioma and neural stem cell - Nasarudin, Mohamad Amirul Imran Mohd (Universiti Sains Malaysia, 2016)
Glioblastoma multiforme (GBM) is the most malignant subtype of brain cancer. Current standard treatment are limited in effectiveness and impose additional side effect. Quercus infectoria (QI) was reported to be anti-carcinogenic and exhibit inherent antioxidant activity. This study evaluated the effect of QI extract on GBM cell line (DBTRG-05MG) and neural stem cell line (H9-hNSC). Soxhlet extraction was performed using 70% and 100% methanol solvent. Antioxidant activity was measured using DPPH free radicals scavenging assay. Cells were cultured and optimal extract concentration was determined via MTT assay. The genomic and proteomic analysis of the Ql-treated cells were performed using real-time PCR and Western Blot respectively. We observed that 100% methanolic QI extract (100%-Met) produced significantly higher yield (78.46%) compared to 70% methanolic QI extract (70%- Met) (43.7%). Despite not significant, 100%-Met showed higher antioxidant activity compared to 70%-Met (94.62% vs 91.33%). 100%-Met (1C5o:70.76 pg/ml) and 70%-Met (ICso:71.55 pg/ml) were found to show anti-DBTRG-05MG proliferation. Following treatment, DBTRG-05MG showed reduced cancer cell marker (PKM2) gene expression. CASP3 gene, a key player in apoptotic pathway was expressed significantly higher in 100%- Met-treated DBTRG-05MG compared to non-treated group. However, CASP3 expression in 100%-Met-treated H9-hNSC was not significantly different to the non-treated control, indicating QI extract did not possess apoptotic effect on H9-hNSC. Similarly, Western Blot analysis produced clear band at 35 kDA which represent caspase-3 protein for treated DBTRG-05MG, but absent in treated H9-hNSC and non-treated control. In conclusion, QI extract is a potential anti-cancer drug with negative cytotoxicity response towards non cancerous cell such as NSCs. Further study is warranted to elucidate the precise effect of reduction ofCD133 expression on H9-hNSC activity and cell integrity.